2009
DOI: 10.4171/jems/180
|View full text |Cite
|
Sign up to set email alerts
|

The cubic nonlinear Schrödinger equation in two dimensions with radial data

Abstract: Abstract. We establish global well-posedness and scattering for solutions to the mass-critical nonlinear Schrödinger equation iut + ∆u = ±|u| 2 u for large spherically symmetric L 2 x (R 2 ) initial data; in the focusing case we require, of course, that the mass is strictly less than that of the ground state. As a consequence, we deduce that in the focusing case, any spherically symmetric blowup solution must concentrate at least the mass of the ground state at the blowup time.We also establish some partial re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
344
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 201 publications
(351 citation statements)
references
References 77 publications
(162 reference statements)
6
344
1
Order By: Relevance
“…Remark 1.24. A closely related result in the spherically symmetric case was established in [Killip et al 2008b, Corollary 1.12], in which it was shown that any blowup of a spherically symmetric Strichartz class solution in two dimensions must concentrate an amount of mass at least equal to the ground state M(Q); the same result in higher dimensions follows by the same argument together with the results in [Killip et al 2007]. Indeed, we will use the results in [Killip et al 2007] to establish the spherically symmetric case of this theorem.…”
Section: Definition 115 (Semi-strong and Semi-strichartz Solutions)mentioning
confidence: 99%
“…Remark 1.24. A closely related result in the spherically symmetric case was established in [Killip et al 2008b, Corollary 1.12], in which it was shown that any blowup of a spherically symmetric Strichartz class solution in two dimensions must concentrate an amount of mass at least equal to the ground state M(Q); the same result in higher dimensions follows by the same argument together with the results in [Killip et al 2007]. Indeed, we will use the results in [Killip et al 2007] to establish the spherically symmetric case of this theorem.…”
Section: Definition 115 (Semi-strong and Semi-strichartz Solutions)mentioning
confidence: 99%
“…The scattering for radially symmetric solutions with L 2 initial data was recently established in [20] for 2d, and in [22] it Q(x), or a blow up solution which is a pseudoconformal image of e it Q(x) (a "self-similar solution"), or a globally defined solution with quadratically decaying in time L 4/d+2 norm which implies scattering as t → ±∞.…”
Section: Furthermore This Nls Equation Enjoys Several Invariances Imentioning
confidence: 99%
“…global existence) for critical equations in the defocusing case, or in focusing cases in which the solution is "smaller" in mass or energy than that of the ground state. See [28], [81], [30] About the author Terence Tao is professor and James and Carol Collins Chair at the Department of Mathematics at the University of California, Los Angeles. He was a recipient of the Fields Medal in 2006 and is a Fellow of the National Academy of Sciences.…”
Section: Further Developmentsmentioning
confidence: 99%